Tissue engineered bone as an alternative for repairing bone defects - Evy Eida Vitria; Benny S. Latif (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Dentist especially oral surgeon, are frequently faced with defect in bone resulting from disease or trauma. If the defect is small, it will frequently has a good healing, however, if the defect is larger, incomplete regeneration often occurs and a fibrous scar results. Transplantation of autogenous bone has been one of the most frequent procedures of reconstructive oral and maxillofacial surgery because it has shown excellent clinical success; however, autogenous bone grafting is often related to disadvantages like limited availability, and donor morbidity. Purpose: The purpose of this review is to explain the basic principles of tissue engineering, background of regeneration process, also advantages and disadvantages of tissue engineered bone compared to autogenous bone graft. Review: Recently, tissue engineered bone provides a promising strategic innovation and becomes a new alternative for bone regeneration process. Tissue engineering is a term originally used to describe tissue produced in isolation and culture by cells seeded in various porous absorbable matrices. Tissue engineering generally combines three key elements (Tissue Engineering Triad) i.e: scaffolds (matrices), signaling molecules (growth factors), and cells (osteoblast, fibroblast, etc). Conclusion: Tissue engineering will facilitate initial bone healing in order to accomplish tissue regeneration process.Latar belakang: Seorang dokter gigi khususnya dokter gigi bedah mulut, seringkali dihadapkan dengan keadaan defek tulang akibat dari suatu penyakit atau trauma. Jika defeknya kecil mungkin dapat sembuh dengan baik, tetapi bila defeknya besar, kemungkinan regenerasi tulang tidak sempurna dan menghasilkan scar/jaringan parut. Transplantasi dengan menggunakan autogenous bone graft meskipun sampai saat ini masih banyak digunakan untuk operasi rekonstruksi di bidang bedah mulut dan maksilofasial karena telah menunjukkan keberhasilan klinik yang cukup baik, namun cara ini mempunyai banyak kekurangan, diantaranya morbiditas dari sisi donor. Tujuan: Tujuan dari penulisan ini adalah untuk menjelaskan tentang prinsip-prinsip dasar tissue engineering, hal-hal yang berperan dalam proses regenerasi serta keuntungan dan kerugian tissue engineering dibandingkan dengan autogenous bone graft. Tinjauan pustaka: Saat ini penggunaan tissue engineered bone merupakan suatu strategi inovatif yang telah dikembangkan dan memberikan suatu alternatif dalam proses regenerasi tulang. Tissue engineering atau rekayasa jaringan merupakan suatu istilah yang digunakan untuk menjelaskan bagaimana suatu jaringan dihasilkan dengan cara isolasi dan kultur sel dalam berbagai matriks porous absorble. Tissue engineering akan melibatkan tiga elemen kunci (tissue engineering triad) yaitu Scaffold (matriks), molekul-molekul signal (growth factors) dan sel-sel (osteoblast, fibroblast, dll). Kesimpulan: Teknik tissue engineering akan memfasilitasiproses awal penyembuhan tulang sehingga proses regenerasi jaringan akan tercapai.